Vontade livre e desvalor da ação no direito penal brasileiro - Ribeiro, Arthur Davis Floriano (2011)
Based on the concept of freedom, this research examines the contours of the right to freedom, especially freedom it´s relates to thought and other mental processes (freedom of will or freedom of thought in the broad sense), within the legal system assumes Brazilian-criminal. To this end, this work seeks to draw a general view about the subjective aspect of criminal law patriotic, examining the subjective elements of typicality, the antilegal and guilt, as well as the subjective conditions that influence the sentencing, not forgetting, even , to emphasize the Brazilian punitive legal system that preachescriminal justice. This examination, which reviews the changes that occurred throughout the history of Brazilian criminal law, intent, moreover, for theories that relate to the theme of subjectivity in the criminal as well as studies in the field of Psychology Personality of Psychoanalysis and Neurobiology, cast doubt on the freedom during the formation of intention (thought) and at the stage of manifestation (manifestation of thought). Thus, this research seeks to check if, in Brazil, today consolidated subjective structuring, which still has traces of retributive, thins the studies that have been held around the limits of human freedom. For the last, the problems pointed out that the Brazilian system has when it comes to the protection of human freedom, especially freedom of thought, this work assumes the task of providing, as appropriate, elements for a possible overhaul of the system. Without claiming to solve all problems related to this subject, this research aims, in short, bring to debate the problem of freedom in the camp of thinking and acting, so that, if possible, can promote a new reflection on the Brazilian penal law and its legitimacy